59‐4: Late‐News Paper: High Transmittance and High Charging Rate 8K 120Hz ADS LCD TV. Issue 1 (25th September 2020) - Hu, Hehe; Yuan, Guangcai; Gu, Zhaoyun; Huang, Jianhua; Ning, Ce; Wang, Baoqiang; Qiu, Yun; Ma, Xiaocheng; Liu, Liwei; Liu, Rui; Li, Zhengliang; Shi, Guangdong; et al.
Abstract : A 65‐inch 8K 120Hz ADS LCD TV based on novel technologies including New Oxide BCE, i‐ADS, DCT‐PS and SSD (Smart Sync Driving), has achieved a high transmittance of 4.0% and a high charging rate of 92%. At the same time, BOE have developed the world's first 110‐inch 8K ADS‐LCD TV with 120Hz‐driven.